An open architecture patient monitoring system using standard technologies. - Varady, P. (IEEE Transactions on information technology in biomedicine)
Computer-aided bedside patient monitoring is applied in areas where real-time vital function analysis takes place. Modern bedside monitoring requires not only the networking of bedside monitors with a central monitor but also other standard communication interfaces. In the paper, an approach to patient monitoring is introduced. A patient monitoring system was developed and implemented based on an existing industry standard communication network, using standard hardware components and software technologies. The open architecture system design offers scalability, standard interfaces, and flexible signal interpretation possibilities.